The attitudes of primary healthcare providers towards web-based training on public health services in rural China: a cross-sectional study. (December 2016) - Zhan, X.X.; Zhang, Z.X.; Sun, F.; Peng, W.J.; Zhang, H.; Yan, W.R.
Abstract: Objectives: To explore the attitudes of primary healthcare workers, including township public health workers (TPHWs) and village doctors (ViDs), towards web-based training on basic public health services (BPHS) and to examine the factors influencing their attitudes. Study design: Cross-sectional study. Methods: Questionnaires addressing training status, needs, and attitudes towards web-based public health training were administered to 2768 primary healthcare workers from May to September 2013. Multivariate logistic regression models were used to identify the factors that were significantly associated with a positive attitude towards web-based public health training. Results: Among the 2768 participants, 90.6% of the TPHWs and 86.9% of the ViDs expressed a positive attitude towards web-based BPHS training. TPHWs who had a positive attitude towards previous public health training (odds ratio [OR] = 2.75, 95% confidence interval [CI] = 1.28–5.93) and better computer skills (OR = 2.59, 95% CI = 1.03–6.48) were more likely to adopt web-based training on BPHS, as were ViDs who had better computer skills (OR = 2.54, 95% CI = 1.58–4.11) and better Internet speeds (neutral: OR = 2.81, 95% CI = 1.58–5.01; satisfied: OR = 2.53, 95% CI = 1.28–5.01). TPHWs who tended to read papers (OR = 0.24, 95% CI = 0.11–0.50) and were aged 50 years or older (OR = 0.34, 95% CI = 0.14–0.87), as were ViDs who tended to read papers (OR = 0.48, 95% CI = 0.29–0.77), expressed a more negative attitude towards web-based BPHS training. Conclusions: The findings indicated that most primary healthcare workers have a positive attitude towards web-based BPHS training. More priority measures, such as conducting computer training, improving Internet quality and integrating mobile technology, are recommended and will further improve the implementation of web-based public health training programs. Highlights: Most primary healthcare workers showed a positive attitude towards web-based basic public health services (BPHS) training. Township public health workers (TPHWs) with previous public health training tended to web-based training on BPHS. Village doctors (ViDs) with better Internet speed were more likely to adopt web-based training on BPHS. Implementing the web-based BPHS training among primary healthcare workers in China is feasible. TPHWs and ViDs with better computer skills or an online-reading preference tended to web-based BPHS training.